Design of HHO Generator to Reduce Exhaust Gas Emissions and Fuel Consumption of Non-Injection Gasoline Engine - Harman Harman; Ahyar Ahyar (Jurnal Dinamika Vokasional Teknik Mesin, 2019)
The continuous increase of fuel consumption has caused fossil fuel shortages, rising its price tremendously. Transportation activities have the largest contribution to air pollution in the form of exhaust gas compared to other industrial activities. Various methods have been used to reduce the air pollution level as well as reducing fuel consumptions, one of which is the use of environmentally friendly fuel gas. The fuel gas is obtained from the electrolysis of water into oxy-hydrogen gas (HHO) as an additive in the fuel combustion process. The research methodology is experimental research which consists of designing and manufacturing of HHO, and field testing. In the planning and manufacturing stages, an HHO generator is produced, equipped with an input voltage regulator in order to produce the gas as needed, with shape and size adapted to the available space on the engine room. The testing stage was conducted on a 1781 cc engine, 2015 Toyota pick up truck which included laboratory test and on the road test. The results show that by activating the HHO generator, there is a reduction of CO and HC emissions, and also a reduction in fuel consumption when compared to the operation of the vehicle at the same load but without HHO generator.Meningkatnya konsumsi bahan bakar minyak secara terus menerus menyebabkan kelangkaan ketersediaan bahan fosil di alam, sehingga harganya menjadi mahal. Kegiatan transportasi menyumbangkan polusi udara dari hasil emisi gas buang kendaraan terbesar dibanding kegiatan industri lainnya. Oleh karena itu dilakukan berbagai cara untuk menurunkan tingkat polusi udara sekaligus menurunkan konsumsi bahan bakar minyak. Salah satunya adalah penggunaan gas bakar ramah lingkungan yang diperoleh dari elektrolisis air gas oksihidrogen (HHO) sebagai bahan tambah dalam proses pembakaran bahan bakar. Metodologi penelitian ini adalah penelitian eksperimental yang terdiri atas perancangan dan pembuatan generator HHO serta pengujian lapangan.  Pada tahap perancangan dan pembuatan dibuat generator gas HHO yang dilengkapi dengan pengatur tegangan input agar menghasilkan gas sesuai kebutuhan, dengan bentuk dan ukuran yang disesuaikan dengan tempat yang tersedia pada ruang mesin. Sedangkan pengujian dilakukan pada Mobil Toyota Kijang Pick Up 1781cc pembuatan tahun 2005 yang meliputi uji laboratorium dan uji jalan di jalan raya.  Hasil yang diperoleh bahwa dengan mengaktifkan generator HHO, terjadi penurunan emisi CO dan HC serta penurunan konsumsi bahan bakar pada beban yang sama, dibandingkan jika kendaraan dioperasikan tanpa generator HHO